Ecosystem-based approach to aquaculture management - White, Patrick; San Diego-McGlone, Maria Lourdes (Science Diliman: A Journal of Pure and Applied Sciences; Vol 20 No 2 (2008), 2009)
Ecosystems have real thresholds and limits which, when exceeded, can affect major system restructuring. Once thresholds and limits have been exceeded, changes can be irreversible. Diversity is important to ecosystem functioning. The ecosystem approach is a strategy for the integrated management of land, water, and living resources that promotes conservation and sustainable use in an equitable way. The application of the ecosystem approach will help to reach a balance of the three main objectives: conservation, sustainable use, and a fair and equitable sharing of the benefits and use of the natural resources. Aquaculture development needs to be within the carrying capacity of the water resource so that it is sustainable and does not greatly impact the environment. The determination of the carrying capacity needs to be science-based. The planning of development in ecosystems has been done for freshwater ecosystems within the PAMB (Protected Area Management Board) framework, but in many cases this does not give the correct significance to the impact of aquaculture on the water resources in the ecosystem. It also needs to be extended to river basins and estuaries, brackishwater areas, and inland bays, and seas. The planning and management of aquaculture needs to be undertaken at the local government unit (LGU) level in a coordinated manner by all the LGUs that have a part of the water resource. The co-management of aquaculture, in terms of monitoring of the environment, monitoring of production, and monitoring of licenses, needs to be funded out of license fees and non-compliance fines collected by the LGUs. A number of these management activities need to be undertaken jointly (monitoring the environment) and others separately but in a coordinated manner (e.g., checking licenses and checking compliance).
Keywords: Aquaculture, ecosystem, management